2003
DOI: 10.1016/s0959-8049(03)00067-4
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyl transpeptidase catalyses the extracellular detoxification of cisplatin in a human cell line derived from the proximal convoluted tubule of the kidney

Abstract: Nephrotoxicity is a side-effect and the main factor limiting the clinical use of cisplatin. In vivo, the administration of the cysteine-containing tripeptide glutathione (GSH) has been found to reduce nephrotoxicity, but the biochemical mechanism of this protective action is not fully understood. The present study was designed to gain insights into the mechanism by which GSH prevents cisplatin nephrotoxicity. We also wanted to verify the hypothesis of whether the protective action of GSH is mediated by product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Preincubation of cells before cisplatin treatment indeed rescued from cisplatin sensitivity by more than 200-fold in RPteC/SV40 from increased sensitivity. these data would suggest that GGt is a "good" activity involved in detoxifiying cisplatin, and are consistent with previously published proposed mechanisms of GGt-dependent resistance to cisplatin (Daubeuf et al, 2002(Daubeuf et al, , 2003Paolicchi et al, 2003). these proposed mechanisms were all based on findings using 2D cell cultures with cell lines that had varying degrees of similarity with RPteCs down to overexpression of GGT in HeLa cells.…”
Section: Ggt In the Extracellular Space Increases Cisplatin Sensitivitysupporting
confidence: 90%
See 2 more Smart Citations
“…Preincubation of cells before cisplatin treatment indeed rescued from cisplatin sensitivity by more than 200-fold in RPteC/SV40 from increased sensitivity. these data would suggest that GGt is a "good" activity involved in detoxifiying cisplatin, and are consistent with previously published proposed mechanisms of GGt-dependent resistance to cisplatin (Daubeuf et al, 2002(Daubeuf et al, , 2003Paolicchi et al, 2003). these proposed mechanisms were all based on findings using 2D cell cultures with cell lines that had varying degrees of similarity with RPteCs down to overexpression of GGT in HeLa cells.…”
Section: Ggt In the Extracellular Space Increases Cisplatin Sensitivitysupporting
confidence: 90%
“…these results led Hanigan and co-workers to the conclusion that cisplatin is successively metabolized by GGT, dipeptidase and finally cystein-conjugate beta-lyase, finally forming an active thiol that causes nephrotoxicity (townsend, 2003;Zhang and Hanigan, 2003). Paolicchi et al (2003) reinterpreted these findings, as it had already been shown that systemic inhibition of GGt by acivicin lead to increased plasmatic levels of GSH in mice (Griffith and Meister, 1979). This finding was corroborated in GGT knockout mice (lieberman et al, 1996).…”
Section: Ggt In the Extracellular Space Increases Cisplatin Sensitivitymentioning
confidence: 90%
See 1 more Smart Citation
“…γ-Glutamyl transpeptidase (γ-glutamyl transferase, GGT), an enzyme located on the outer surface of the plasma membrane, catalyzes the transfer of the γ-glutamyl moiety from glutathione (GSH), glutathione S-conjugates, or other γ-glutamyl compounds to γ-glutamyl acceptors such as amino acids, dipeptides, or H 2 O. GGT plays key roles in the maintenance of glutathione homeostasis [1][2][3][4][5][6][7] and metabolism of biomolecules such as leukotriene C4 and xenobiotics following their conjugation with GSH [8].…”
Section: Introductionmentioning
confidence: 99%
“…A study of U937 lymphoma cells found that γ-GTP may play a role in anti-apoptotic signaling (36). A study has confirmed that cysteinyl-glycine, which is catalyzed by γ-GTP, is able to form complexes with cisplatin and that such adducts are not readily transported through the cell membrane (37). These mechanisms are thought to account for the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%